Application of Treated Sewage Effluent for Watering of Public Park and Landscape Garden - Mohd. Said, Mohd. Ismid (Penerbit UTM, 2008)
Water shortages, combined with increasing water pollution are causing widespread public health problems, limiting economic and agricultural development and harming a wide range of ecosystems. A report by the Secretary General of the United Nations Commission on Sustainable Development (1997) concluded that there is no sustainability in the current uses of fresh water by either developing or developed nations. The report states that worldwide water usage has been growing at more than three times the world’s population The rapid development and industrialisation of Malaysia for the past two decades have affected the water resources of the country especially in highly urbanised areas. Furthermore, deteriorating water quality of many rivers is also a contributing factor to the water woes of Malaysia. One of the major sources of water pollution in Malaysia is sewage, in which the country produces 5 million tonnes annually (DOE, 1997). Under these circumstances, the problems of river pollution and water shortages can be reduce if waste products like treated sewage effluent can be applied to other beneficial uses. This study was conducted by assessing public perception of using treated sewage effluent for the watering of public parks and landscape garden at residential areas in the city Johor Bahru, Johor. Residents of four residential areas were surveyed for public opinions with regard to using sewage effluent for watering of public parks and landscape gardens. These residential areas were selected based on the size and availability of public parks in the areas, and also on the size and capacity of its sewage treatment plant.